Identification of a New Serine Alkaline Peptidase from the Moderately Halophilic Virgibacillus natechei sp. nov., Strain FarDT and its Application as Bioadditive for Peptide Synthesis and Laundry Detergent Formulations. (30th November 2019) - Mechri, Sondes; Bouacem, Khelifa; Amziane, Meriam; Dab, Ahlem; Nateche, Farida; Jaouadi, Bassem
Abstract : A new peptidase designated as SAPV produced from a moderately halophilic Virgibacillus natechei sp. nov., strain FarD T was investigated by purification to homogeneity followed by biochemical and molecular characterization purposes. Through optimization, it was determined that the optimum peptidase activity was 16, 000 U/mL. It was achieved after 36 h incubation at 35°C in the optimized enzyme liquid medium (ELM) at pH 7.4 that contains only white shrimp shell by-product (60 g/L) as sole energy and carbon sources. The SAPV enzyme is a monomer protein with a molecular mass of 31 kDa as estimated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and high-performance liquid chromatography (HPLC) gel filtration chromatography. The sequence of its NH2 -terminal amino-acid residues showed homology with those of Bacillus peptidases S8/S53 superfamily. The SAPV showed optimal activity at pH 9 and 60°C. Irreversible inhibition of enzyme activity by diiodopropyl fluorophosphates (DFP) and phenylmethanesulfonyl fluoride (PMSF) confirmed its belonging to the serine peptidases. Considering its interesting biochemical characterization, the sapV gene was cloned, sequenced, and heterologously overexpressed in the extracellular fraction of E. coli BL21(DE3)pLysS. The biochemical properties of the recombinant peptidase (rSAPV) were similar to those of the native one. The highest sequence identity value (97.66%) of SAPV was obtained with peptidase S8 from Virgibacillus massiliensis DSM 28587, with 9 amino-acid residues of difference. Interestingly, rSAPV showed an outstanding and high resistance to several organic solvents than SPVP from Aeribacillus pallidus VP3 and Thermolysin type X. Furthermore, rSAPV exhibited an excellent detergent stability and compatibility than Alcalase 2.4 L FG and Bioprotease N100L. Considering all these remarkable properties, rSAPV has attracted the interest of industrialists.